An introduction to the textual criticism of the New testament - Robertson, Archibald Thomas, 1863-1934 (London, UK Hodder and Stoughton, 1925)
Includes bibliographical references and indexes.
Well annotated. Donated by Dr L.L. Edwards.
Keywords: Bible. N.T. -- criticism, interpretation, etc